OPERATIONAL RESEARCH MODELS IN HUMAN RESOURCES MANAGEMENT - Velásquez Pino, Carmela Catalina (2008)
In the University faculties, as in every organization, there are Organizational entities that have functions related to human resource management, such as the administrative management, academic department, faculties, even the committee assessment and the theaching improvement. In the context described above, our interest is to develope a study concerned with the following objectives: To have an assignment system charge of the professors of the Mathematic Science Faculty, in particular in the Operational Research deparment, which guarantees an objective and impartial distribution that will allow to select the suitable professor to teach a particular course, with this purpose, it has been formulated a linear program model. Moreover, we set out a Markov's chain which translate in a transition probability matrix the changes of category of the permanent professor of the Mathematic Science Faculty among consecutives professor promotion procedure.